Associations between serum lipid profiles and the incidence of chronic obstructive pulmonary disease in the UK Biobank - Mengxia Li; Bingqing Xu; Hao Yu; Yanan Wan; Zheng Zhu; Pengfei Luo; Jian Su; Jinyi Zhou; Xikang Fan (Journal of Health, Population and Nutrition)
Abstract Objective To investigate the relationship between serum lipid levels and the risk of Chronic obstructive pulmonary disease (COPD) in the UK Biobank. Methods We performed this prospective study in 381,938 adults without COPD from UK Biobank. Serum high-density cholesterol (HDL-C), low-density cholesterol (LDL-C), total cholesterol (TC), triglyceride (TG), apolipoprotein A (ApoA) and apolipoprotein B (ApoB) were measured and classified into quintiles. Restricted cubic spline (RCS) analysis was applied to visualize the dose-response relationship between lipids and COPD risk and Cox proportional hazard models to calculate hazard ratios (HRs) and 95% confidence intervals (CIs). Results We documented 10,443 incident COPD cases. Nonlinear relationships were found between HDL-C, LDL-C, TC, ApoA, ApoB and COPD risk with RCS analysis (P values for non-linearity < 0.05). Accordingly, multivariable-adjusted regression analysis indicated abnormal HDL-C and ApoA, and low LDL-C, TC and ApoB were associated with increased risk of COPD. Compared to intermediate quintile (Q3) group, both high or low HDL-C and ApoA were associated with risk of COPD. Corresponding HRs (95% CIs) were 1.15 (1.08–1.22), 1.16 (1.09–1.23) in Q1 group and 1.08 (1.01–1.16), 1.07 (1.00-1.14) in Q5 group. For LDL-C, TC and ApoB, there were more than 29% higher risk was observed in Q1 group with HRs (95% CIs) of 1.34 (1.27–1.42), 1.38 (1.30–1.46) and 1.29 (1.21–1.37), while HRs (95% CIs) were 0.88 (0.83–0.94), 0.92 (0.86–0.98) and 0.90 (0.84–0.95) in Q5 groups. We also observed the interactions between specific lipids and age at recruitment, sex and smoking status with stratified analysis. Conclusions Our study provides the first evidence demonstrating the associations between six major serum lipids and COPD risk, revealing multiple nonlinear relationships. There were U-shaped associations between serum HDL-C, ApoA and COPD risk, and L-shaped associations between LDL-C, TC, ApoB and COPD risk.